Pengaruh Persepsi Harga, Promosi dan Citra Merek terhadap Keputusan Pembelian : (Studi pada Pengguna Alfagift) - Intan Fitri Dwi Hardono; Rina Ayu Vildayanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The purpose of this study was to determine the effect of Price Perception, Promotion, and Brand Image on Purchasing Decisions. The sample in this study were 100 Alfagift users, with the sampling method using Non Probability Sampling with Accidental Sampling technique. Data collection by distributing questionnaires. The research instrument was a questionnaire with a Likert Scale. The method used in this research is quantitative method. The results of the respondents' answers to the questionnaire given were then processed using SPSS software version 26. The results showed that Price Perception and Brand Image have a significant effect on Purchasing Decisions, Promotion has no significant effect on Purchasing Decisions, and Price Perception, Promotion and Brand Image simultaneously affect Purchasing Decisions.